COMMUNITY STRUCTURE OF BUTTERFLIES (LEPIDOPTERA: PAPILIONOIDEA) IN SUMUR PANGURIPAN CULTURAL RESERVE AREA, SURABAYA CITY, EAST JAVA - Siti Zulaikha; Muhamad Azmi Dwi Susanto (ZOO INDONESIA, 2022)
The Sumur Panguripan Cultural Reserve is an area located in an urban area with environmental conditions that are still maintained and that also has various types of vegetation. Research data on the structure of butterfly communities in urban areas, especially the city of Surabaya, is still very minimal, so this research is very important to do. This study aims to determine the structure of the butterfly community in the Sumur Panguripan Cultural Reserve area of Surabaya city. The observation method was used in this study to collect data by directly counting the species and number of butterfly individuals or by using the visual encounter survey, and the path of observation was determined using the transect line method. In this study, results showed 108 individuals from 22 species, consisting of 5 families, with a diversity index value of H' = 2.93. The value of the butterfly species diversity index in closed habitat types H = 2.68 is lower than the butterfly diversity index value in open habitat types H = 2.72. The results of the butterfly diversity index in both habitat types indicate that this area has a medium diversity category. The diversity and number of butterfly individuals in both habitat types can be used to describe a fairly stable community structure in the Sumur Panguripan Cultural Reserve area.